Diagnosis, prevalence, and mortality of sarcopenia in dialysis patients: a systematic review and meta‐analysis. Issue 1 (5th January 2022) - Shu, Xiaoyu; Lin, Taiping; Wang, Hui; Zhao, Yanli; Jiang, Tingting; Peng, Xuchao; Yue, Jirong
Abstract: There is no consensus on the prevalence of sarcopenia or its impact on mortality in end‐stage renal disease patients undergoing dialysis. This review aimed to summarize the diagnostic criteria of sarcopenia and its prevalence and impact on the mortality of end‐stage renal disease patients undergoing dialysis. Embase, MEDLINE, PubMed, and Cochrane Library were searched from inception to 8 May 2021 to retrieve eligible studies that assessed muscle mass by commonly used instruments, such as dual‐energy X‐ray absorptiometry, bioelectrical impedance analysis, magnetic resonance imaging, and body composition monitor. Two assessment tools matched to study designs were employed to evaluate study quality. Pooled sarcopenia prevalence was calculated with 95% confidence interval (CI), and heterogeneity was estimated using the I 2 test. Associations of sarcopenia with mortality were expressed as hazard ratio (HR) and 95% CI. The search identified 3272 studies, and 30 studies (6162 participants, mean age from 47.5 to 77.5 years) were analysed in this review. The risk of bias in the included studies was low to moderate. Twenty‐two studies defined sarcopenia based on low muscle mass (LMM) plus low muscle strength and/or low physical performance, while eight studies used LMM alone. Muscle mass was assessed by different instruments, and a wide range of cut‐off points were used to define LMM. Overall, sarcopenia prevalence was 28.5% (95% CI 22.9–34.1%) and varied from 25.9% ( I 2 = 94.9%, 95% CI 20.4–31.3%; combined criteria) to 34.6% ( I 2 = 98.1%, 95% CI 20.9–48.2%; LMM alone) ( P = 0.247 between subgroups). The statistically significant differences were not found in the subgroups of diagnostic criteria ( P > 0.05) and dialysis modality ( P > 0.05). Additionally, the sarcopenia prevalence could not be affected by average age [regression coefficient 0.004 (95% CI: −0.005 to 0.012), P = 0.406] and dialysis duration [regression coefficient 0.002 (95% CI −0.002 to 0.005), P = 0.327] in the meta‐regression. The pooled analyses showed that combined criteria of sarcopenia were related to a higher mortality risk [HR 1.82 ( I 2 = 26.3%, 95% CI 1.38–2.39)], as was LMM [HR 1.61 ( I 2 = 26.0%, 95% CI 1.31–1.99)] and low muscle strength [HR 2.04 ( I 2 = 80.4%, 95% CI 1.19–3.5)]. Although there are substantial differences in diagnostic criteria, sarcopenia is highly prevalent in dialysis patients and is linked to increased mortality. The standardization of sarcopenia diagnostic criteria would be beneficial, and future longitudinal studies are needed to investigate the prevalence and prognostic value of sarcopenia in dialysis patients.